Excess Li2O Additives to Promote Grain Boundary Growth and Improve Ionic Conductivity of LiTa2PO8 Solid Electrolytes - Zhang, Qian; Meng, Fuhai; Liao, Ruixiong; Chen, Long; Xu, Mengqian; Zhong, Shengwen; Chen, Jun; Lu, Anxian (Frontiers in Materials, 2021)
LiTa2PO8(LTPO) is a new solid-state lithium ion electrolyte material reported in the latest research, which has high bulk ionic conductivity and low grain boundary ion conductivity. However, it is difficult to densify with conventional sintering methods. Herein, in this work, the solid-phase synthesis method was used to prepared the LTPO solid-state electrolyte, and the influence of the amount of lithium on the structure and performance of LTPO electrolyte material was investigated. The results show that the excess Li2O does not increase other impurities and does not change the structure of the material, but the liquid phase produced by the excess Li2O can promote the elimination of interfacial pores, accelerate the direct bonding of grains and improve the ionic conductivity of grain boundary, thus improving the overall ionic conductivity of the material. Considering the volatilization of lithium and the impact of liquid phase sintering at high temperatures and the content restructuring, after adding 20wt% excess formulation of Li2O, the resultant of LTPO density is 5.0g/cm3, the density reaches 85.58%. As a result, the total ionic conductivity of the electrolyte is 3.28×10-4 S/cm at 25 oC, and the Li-ion diffusion activation energy is 0.27 eV. In addition, after loading this electrolyte into a Li-Li symmetric battery, it is proved that the electrolyte has lithium ion transport performance and can be used in all-solid-state batteries. However, it is also found from cyclic voltammetry (CV) and X-ray photoelectron spectroscopy (XPS) analysis that the interface between LTPO material and Li is unstable, and Ta5+ ions are reduced, which will be another key issue to be addressed in the future.